TWO-MATRIX PHOTOMETER CONTROL SYSTEM - Zhantayev, Zh. Sh.; Kuratov, K. S.; Seytimbetov, A. M.; Mailybayev, A. T.; Alimgazinova, N. Sh.; Manapbayeva, A. B.; Kuratova, A. K.; Iztleuov, N. T. (Одеські астрономічні публікації, 2016)
In this paper astronomical two-matrix photometer is described. It differs from common one CCD camera photometers by using the second CCD camera. It enables simultaneously to carry out the studied star and standard star light inputs measurements. The second camera application enables significantly to increase measurements accuracy and at least twice time decrease of one star observation. The significant increase of measurements accuracy is reached by carrying out simultaneous observations, and errors caused by the Earth atmosphere fluctuation are the same as for studied star so for standard star. Time decrease is reached by carrying out both stars simultaneous observations. In the paper photometer’s optical mechanics scheme is given. The motion mechanism of receiving and recording block with micrometer screw rotated by stepping motor is described. It is demonstrated that exact coordinates of matrix position attached to clutch on micrometer screw are shoot by absolute magnetic encoder. The applied two-matrix photometer control system electronic equipment is described. The photometer operation control algorithm installed on Tien-Shan astronomical observatory 1-meter telescope is presented.